Factors associated with feeding practices and stunting among children aged 6-23 months in Dalits and non Dalits of Dhanusha district. - Sah, Anil Kumar (2017)
SUMMARY: Nutrition is fundamental of survival, growth and development . Nutrition well being is and essential of fastest achievement of Sustainable Development Goals(SDG). The first two years of life is a window of opportunity to prevent undernutrition. Undernutrition represents 45% of all the death globally. There are many factors that affects children's nutrition status such as inappropriate feeding practices, less diversified food, socio-economic and health factors. Dalits are the unprivileged population of Nepal. This study aims to assess factors associated with feeding practices and stunding of children among 6-23 months in Dalits and Non-Dalits of Dhanusha district using some indicators recommended by WHO as well as their associated factors. This study design was community based cross-sectional comparative study and the use of quantitative method. The study sites were nine village Development committees (VDCs) of Dhanusha district of three electoral constituencies . The sample size for the study was 598 for both groups (298 for Dalits and 300for Non-Dalits). The stunting among children were measured by using anthropometric measure (length) and their mothers interviewed by using structured questionnaire about feeding practices and socio-economic, demographic and health related factors.Data entry was done by using Epidata 3.1 version and analysis was done by using International Business Machines (IBM) statistical analysis (Enter Method) used to show statistical association between dependent and independent variables. The mothers with correct knowledge on minimum dietary diversity was found about 64 percent and 71% in Dalits and Non-Dalits respectively . Mothers with correct knowledge on minimum acceptable diet was found about 53% nad 60% respectively. Minimum dietary diversity and minimum acceptable diet practices of children were found about 56% and 44% in both groups. Moderately stunting was found 32% and 27% in Dalits and Non-Dalits respectively. Minimum dietary diversity practices were found significantly associated with child morbidity and mother's knowledge on child feeding . Similarly, minimum acceptable diet practices were found significantly associated with age of index child, child morbidity and knowledge on child feeding.maternal education can likely to lead improved complementary feeding practices through various way including improved knowledge, access to health care services and household resource. In Non-Dalits stunting was significantly associated with types of family, age of index child mother's education, father's education and durationof food sufficiency by bivariate analysis. In bivariate analysis , size of house hold, types of family, mass media exposure and mothers with knowledge on child feeding was significantly associated with stunting in Dalits. Children aged 12-23 months were found near about two times more likely to be stunted as compared to children aged 6-11 months in Non-Dalits after adjusting confounding variables. Nepal Demographic Health Survey,2006 and 2011 and Multiple Cluster Indicators shows that children aged 12-23 had high proportion of stunting as compared to 6-11 months. In Dalits, there was no any significant association between stunting and explanatory variables of the study while adjusting the confounders. The stud suggests the need of further research using qualitative method to explore overall underlying factors including cultural practices and belief systems linked with the feeding practices. There should be a focus on awareness raising programme at community level especially among Dalits to improve knowledge for enhancing infant and young child feeding practices as per recommended and also focus on nutritional intervention for stunting.